Analisis Pemilihan Seach Engine Google Sebagai Media Informasi Bagi Mahasiswa Universitas Islam Riau - Lili Handayani; Gusti Maya Sari; Fera Yulia (Jurnal Gema Pustakawan, 2024)
In an effort to meet their information needs, many students rely on search engines, with Google as their main choice. Google as one of the largest and most dominant search engines. Search engine users only need to use keywords regarding the subject they are looking for, to explain that the study material available on the internet and search engines can be varied, ranging from text, sound, images, films, animations, games and other multimedia applications. This research aims to analyze the choice of Google as a search engine by students visiting the Riau Islamic University library. As an information medium. The research method used is a qualitative method. In this research, 10 selected students were selected as resource persons who were visitors to the Riau Islamic University library who accessed the internet. Data collection techniques use observation, interviews and documentation. This research was conducted from August to October 2023. The research results show that the choice of Google search engine by visitors to the Riau Islamic University library is due to the need for information and satisfaction in searching or searching. The factors that influence students in choosing the Google search engine are Focused use as a search engine, popular, speed of access and sophisticated features make the user experience more practical and efficient. There are two important points why Riau Islamic University students are dominant in using the Google search engine. namely about information needs and satisfaction in using the Google search engine.